Polyester plastic imitation stainless steel plastic coated wire and preparation method thereof
By using polyester plastic imitation stainless steel plastic-encapsulated wire design and using two layers of plastic inside and outside to wrap the metal wire, the problem of insufficient mechanical properties of the existing plastic-encapsulated wire is solved, and the tensile, impact and bending strength is significantly improved, and its application scenarios are expanded.
Patent Information
- Application Number
- CN202410868846.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-23
- Filing Date
- 2024-06-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-06-28
AI Technical Summary
The mechanical properties of existing plastic-encapsulated wires cannot meet a variety of usage scenarios, especially in applications where bending resistance is required.
The design of polyester plastic imitation stainless steel plastic-encapsulated wire is adopted. The plastic-encapsulated wire is composed of two layers of plastic-encapsulated metal wires inside and outside. The plastic-encapsulated layer is composed of PET plastic particles, quartz sand and additives. The plastic-encapsulated layer is composed of polyethylene terephthalate/cyclohexane-4-ene-1,2-diyldimethyl ester copolyester, colorant, additive and functional additive.
The tensile strength, impact strength and bending strength of the plastic wrap wire have been significantly improved, expanding its use scenarios, especially in applications that require bending resistance.
Smart Images

Figure CN118866437B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic-coated wires, and more specifically discloses a polyester plastic imitation stainless steel plastic-coated wire and a preparation method thereof. Background Art
[0002] Metal wire is made of metal coils, round coils or metal bars as raw materials, and is processed through professional equipment such as wire drawing equipment and annealing equipment. After multiple drawing, annealing, re-drawing, re-annealing and other processes, it is processed into various filamentary or linear products of different specifications and models. This product is called metal wire. The use of metal wire is very common. It can be used to bundle materials, folded into various pendants, and prepared into various buckles. Common metal wires are exposed to the air as a whole and will oxidize in contact with the air, causing the metal wire to oxidize and rust, causing the metal wire to lose its original luster and affecting its use effect. Only commercial polyolefin, polyester or polyamide materials are used as plastic coating, and the mechanical properties of the products obtained are often unable to meet the multiple usage scenarios of plastic coated wires. Summary of the invention
[0003] The present invention mainly provides a polyester plastic imitation stainless steel plastic-coated wire and a preparation method thereof, which can solve the problem that the mechanical properties of the product often cannot meet the requirements of multiple usage scenarios of the plastic-coated wire.
[0004] To solve the above technical problems, according to one aspect of the present invention, more specifically, a polyester plastic imitation stainless steel plastic coated wire is composed of an internal metal wire, an inner plastic coating layer wrapped around the outside of the metal wire, and an outer plastic coating layer wrapped around the outside of the inner plastic coating layer;
[0005] The inner plastic coating layer is composed of the following components by weight: 87-99.99 parts of PET plastic particles, 1-3 parts of quartz sand, and 0-2 parts of plastic production additives;
[0006] The outer plastic coating layer is composed of the following components in parts by weight: 87-99.99 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester, 0.01-3 parts of a colorant, 0-2 parts of a plastic production additive, and 0-2 parts of a plastic functional additive.
[0007] Furthermore, the metal wire is one of iron wire, steel wire, galvanized iron wire and galvanized steel wire.
[0008] Furthermore, the colorant is one of a white colorant, a red colorant, and a yellow colorant, the plastic production additive is a lubricant pentaerythritol stearate, and the plastic functional additive is an antioxidant 168.
[0009] Furthermore, the thickness of the inner plastic coating layer is 0.02-2 mm.
[0010] Furthermore, the thickness of the outer plastic coating layer is 0.02-1 mm.
[0011] Furthermore, the cross-sectional area of the metal wire is 0.05-100 mm 2 .
[0012] Furthermore, the cross-section of the plastic-coated wire is circular, elliptical, triangular, C-shaped, diamond-shaped or trapezoidal.
[0013] According to another aspect of the present invention, there is provided a method for preparing a polyester plastic imitation stainless steel coated wire, comprising the following steps:
[0014] S1. Preparation of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester: terephthalic acid, cyclohexane-4-ene-1,2-dimethyl dimethanol, ethylene glycol and tetraethyl titanate are added to a reactor, and an esterification reaction is carried out under a nitrogen pressure of 0.5 MPa. The esterification temperature is 230-280°C, and the temperature of the esterification distilled water is controlled at 120-130°C. When the water output reaches 94% of the theoretical value, the esterification is completed. After the esterification reaction is completed, the product is introduced into a polycondensation reactor, and then slowly evacuated to a vacuum degree of no more than 40Pa, and polycondensed at about 270-290°C for 3h. After breaking the vacuum, the material is discharged under stirring, and pelletized and dried to obtain copolyester slices. The molar ratio of terephthalic acid: cyclohexane-4-ene-1,2-dimethyl dimethanol: ethylene glycol: tetraethyl titanate is 1:0.4:0.8:0.01. Preferably, the esterification temperature is 240-260°C, the polycondensation temperature is 270-280°C, and the molar ratio of terephthalic acid: cyclohexane-4-ene-1,2-diyldimethanol: ethylene glycol: tetraethyl titanate is 1: 0.4-0.5: 0.8: 0.01; more preferably, the esterification temperature is 240°C, the polycondensation temperature is 280°C, and the molar ratio of terephthalic acid: cyclohexane-4-ene-1,2-diyldimethanol: ethylene glycol: tetraethyl titanate is 1: 0.4: 0.8: 0.01.
[0015] S2, preparation of the raw material for the inner plastic coating layer: the following components are mixed uniformly according to weight, 87-99.99 parts of PET plastic particles, 1-3 parts of quartz sand, and 0-2 parts of plastic production aids to prepare the raw material for the inner plastic coating layer, and added to the extruder 1, and the temperature of the extruder 1 is set to 120-350°C. Preferably, 92-97 parts of PET plastic particles, 2-3 parts of quartz sand, 0-1 part of plastic production aids, and the temperature of the extruder is set to 220-320°C; more preferably, 97 parts of PET plastic particles, 2 parts of quartz sand, 1 part of plastic production aids, and the temperature of the extruder 1 is set to 300°C.
[0016] S3. Preparation of raw materials for outer plastic coating layer: the following components are prepared by uniformly mixing according to weight parts: 87-99.99 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-diyl dimethyl terephthalate copolyester, 0.01-3 parts of colorant, 0-2 parts of plastic production additives and 0-2 parts of plastic functional additives to prepare the raw materials for outer plastic coating layer, and added to extruder 2. The temperature of extruder 2 is set to 110-250°C. Preferably, 91-97 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester, 0.05-1 part of colorant, 0-1 part of plastic production aid, 0-1 part of plastic functional additive, and the extruder temperature is set to 120-250°C; more preferably, 97 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester, 0.5 part of colorant, 1 part of plastic production aid, 1 part of plastic functional additive, and the extruder temperature is set to 200°C.
[0017] S4, the plastic coating layer raw materials prepared in steps S2 and S3 are combined and extruded through a double-channel composite die head, the inner layer flow channel is the inner plastic coating layer raw material, and the outer layer flow channel is the outer plastic coating layer raw material, and the metal wire passes through the middle of the discharge port of the extruder composite die head so that the outer side of the metal wire is evenly wrapped with the inner plastic coating layer and the outer plastic coating layer.
[0018] S5, sending the metal wire wrapped with the inner plastic layer and the outer plastic layer into 5-35°C water for cooling and winding to complete the preparation of the polyester plastic imitation stainless steel plastic-coated wire. Preferably, during the preparation of the polyester plastic imitation stainless steel plastic-coated wire, the metal wire advances at a speed of 50-300 m / min.
[0019] The polyester plastic imitation stainless steel plastic-coated wire and the preparation method thereof of the present invention have the following beneficial effects:
[0020] (1) The self-made polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester was used as the outer plastic coating material, which significantly improved the mechanical properties of the coating layer and greatly improved the tensile strength, impact strength and flexural strength of the product.
[0021] (2) A two-layer plastic coating structure is adopted. The purpose of the inner plastic coating is to use commercial and low-cost PET as the inner plastic coating layer, reduce the amount of homemade polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester used in the outer plastic coating, and greatly reduce the manufacturing cost.
[0022] (3) Adding quartz sand to the inner plastic coating formula increases the adhesion between the inner and outer plastic coatings, which not only avoids the addition of compatibilizers and reduces production costs, but also further improves the peeling force, making the quality of the plastic-coated wire better.
[0023] (4) The polyester plastic imitation stainless steel plastic coated wire prepared by the present invention not only has the advantages of traditional metal plastic coated wire, such as effectively protecting the metal wire, allowing the metal wire to retain its own metallic luster for a long time, passivating the broken cross section, and being more suitable for users with metal allergies. In addition, the mechanical properties of the polyester plastic imitation stainless steel plastic coated wire have been greatly improved, expanding the application scenarios of the plastic coated wire, especially in products that require anti-bending. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0025] Figure 1 It is a schematic diagram of the structure of the plastic-coated wire.
[0026] In the figure: 1. Metal wire; 2. Inner plastic coating layer; 3. Outer plastic coating layer. DETAILED DESCRIPTION
[0027] The present invention will be described in detail below with reference to the accompanying drawings and in combination with embodiments. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other without conflict.
[0028] Example 1
[0029] Preparation of polyethylene terephthalate / cyclohexane-4-ene-1,2-diyl dimethyl terephthalate copolyester: 16.6 kg of terephthalic acid, 5.7 kg of cyclohexane-4-ene-1,2-diyl dimethanol, 5.0 kg of ethylene glycol and 0.2 kg of tetraethyl titanate are added to a 100L reactor, and an esterification reaction is carried out under a nitrogen pressure of 0.5 MPa, the esterification temperature is 240°C, and the temperature of the esterification distilled water is controlled at 120-130°C; the esterification reaction is stopped when the water output reaches 94% of the theoretical value; after the esterification reaction is completed, the product is introduced into a condensation reactor, and then slowly evacuated to a vacuum degree of no more than 40 Pa, condensed at 280°C for 3 hours, and after breaking the air, the material is discharged under stirring, and pelletized and dried to obtain copolyester slices.
[0030] Melting point determination: Take the polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester slice prepared in Example 1, cut it into a disc with a diameter of about 1 mm, place it on a glass slide, put it in a melting point apparatus, adjust the sight glass until it is clear; the heating rate is 6°C / min, and the heating rate is reduced to 0.5°C / min before approaching the melting point 3°C, and the measurement is repeated three times to record the melting point.
[0031] test 1 2 3 Melting point 142.2-146.5℃ 143.2-146.8℃ 142.5-146.7℃
[0032] Tensile strength determination: The sample of Example 1, commercially available PET particles, and commercially available copolyester particles were prepared into 1A type standard samples, and then tested according to GB / T 1040.2-2006, with a tensile speed of 50 mm / min.
[0033] Impact strength: Refer to GB / T 1043.1-2008 test specimen notched impact strength.
[0034] The test results are as follows:
[0035] sample Impact strength Tensile Strength Bending Strength Example 1 Copolyester 8.9KJ / m2 85.6MPa 97.7MPa Commercially available PET particles 2.4KJ / m2 33.2MPa 48.8MPa Commercially available copolyester particles 5.3KJ / m2 55.4MPa 61.6MPa
[0036] Test conclusion: The polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester prepared in Example 1 of the present invention has greater tensile strength, impact strength and flexural strength than commercially available PET particles and copolyester particles. This shows that the copolyester prepared by modifying cyclohexane-4-ene-1,2-dimethyl dimethyl terephthalate has greatly improved mechanical properties.
[0037] Example 2
[0038] Weigh the following materials by weight: 97 parts of PET plastic particles, 1 part of quartz sand, and 1 part of plastic production aid pentaerythritol stearate, and mix them evenly to prepare the raw materials of the inner plastic coating layer 2, and add them to the extruder 1, and the temperature of the extruder is set to 300°C;
[0039] Weigh the following materials in parts by weight: 97 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester, 0.5 parts of white colorant, 1 part of plastic production additive pentaerythritol stearate, and 1 part of plastic functional additive antioxidant 168, mix them evenly to prepare the raw material of the outer plastic layer 3, add them into extruder 2, and set the temperature of the extruder to 200°C;
[0040] The raw materials of the inner and outer plastic coating layers prepared in the above steps are combined and extruded through a double-channel composite die head, the inner channel is the raw material of the inner plastic coating layer 2, and the outer channel is the raw material of the outer plastic coating layer 3. The iron wire 1 passes through the middle of the discharge port of the extruder composite die head, and the forward speed of the iron wire is 200 meters / min. The screw pressure and speed of the extruder are controlled, and the thickness of the inner plastic coating layer 2 is 1mm, and the thickness of the outer plastic coating layer 3 is 0.5mm;
[0041] The iron wire 1 wrapped with the inner plastic coating layer 2 and the outer plastic coating layer 3 is sent into 15° C. water for cooling and winding to prepare a polyester plastic imitation stainless steel plastic coated wire 1.
[0042] Example 3
[0043] The difference between the plastic-coated wire prepared in Example 3 and Example 2 is that the formula of the inner plastic-coated layer 2 is different. The specific formula is as follows: 97 parts of PET plastic particles, 2 parts of quartz sand, and 1 part of plastic production additives are evenly mixed to prepare the raw materials for the inner plastic-coated layer 2, and added to extruder 1. The temperature of extruder 1 is set to 300°C; the other preparation processes are the same as in Example 2, and polyester plastic imitation stainless steel plastic-coated wire 2 is prepared.
[0044] Example 4
[0045] The plastic-coated wire prepared in Example 4 is different from that in Example 1 in that the formula of the inner plastic-coated layer 2 is different. The specific formula is as follows: 97 parts of PET plastic particles, 3 parts of quartz sand, and 1 part of plastic production additives are evenly mixed to prepare the raw materials for the inner plastic-coated layer 2, which are added to extruder 1, and the temperature of extruder 1 is set to 300°C; the other preparation processes are the same as in Example 2, and polyester plastic imitation stainless steel plastic-coated wire 3 is prepared.
[0046] Example 5
[0047] The difference between the plastic-coated wire prepared in Example 5 and Example 1 is that the formula of the inner plastic-coated layer 2 is different. The specific formula is as follows: 97 parts of PET plastic particles and 1 part of plastic production additives are evenly mixed to prepare the raw materials for the inner plastic-coated layer 2, and added to extruder 1. The temperature of extruder 1 is set to 300°C; the other preparation processes are the same as in Example 2, and polyester plastic imitation stainless steel plastic-coated wire 4 is prepared.
[0048] Peel force measurement: Using an intelligent tensile testing machine according to GB / T1040.3-2006 standard, the plastic-coated wires prepared in Examples 2-4 were tested at room temperature except for the inner plastic-coated layer 2 and the outer plastic-coated layer 3 of the iron wire 1. The outer plastic-coated layer 3 was placed on the lower fixture, and the inner plastic-coated layer 2 was placed on the upper fixture. The test was conducted under the following test conditions: temperature 20±2°C, humidity 45-70%, sample size 75mm×15mm, tensile speed 50mm / min, fixture interval length 50mm, and the test was repeated five times. The test results are shown in the following table:
[0049] test 1 2 3 4 5 average value Plastic coating line 21.2N 21.3N 20.8N 21.4N 21.0N 21.1N Plastic coating line 2 26.5N 26.3N 26.2N 26.7N 25.9N 26.3N Plastic coating line three 19.4N 19.4N 19.2N 19.6N 19.4N 19.4N Plastic coating line 4 12.1N 12.6N 12.5N 12.8N 12.4N 12.5N
[0050] Test conclusion: From the peeling force data results of the fourth coating line, it can be seen that the peeling force between the inner coating layer 2 and the outer coating layer 3 is not low, and the compatibility between PET plastic and the polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester prepared by the present invention is good; after adding quartz sand to the formula of the inner coating layer 2, the peeling force between the inner coating layer 2 and the outer coating layer 3 is significantly increased, and the optimal addition amount is 2 parts (coating line 2).
[0051] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention also fall within the protection scope of the present invention.
Claims
1. A polyester plastic imitation stainless steel coated wire, characterized by: The plastic-coated wire is composed of an inner metal wire (1), an inner plastic-coated layer (2) wrapped around the outer side of the metal wire (1), and an outer plastic-coated layer (3) wrapped around the outer side of the inner plastic-coated layer (2); The inner plastic coating layer (2) is composed of the following components in parts by weight: 87-99.99 parts of PET plastic particles, 1-3 parts of quartz sand, and 0-2 parts of plastic production additives; The outer plastic coating layer (3) is composed of the following components in parts by weight: 87-99.99 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester, 0.01-3 parts of a colorant, 0-2 parts of a plastic production additive, and 0-2 parts of a plastic functional additive; The preparation method of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester is as follows: terephthalic acid, cyclohexane-4-ene-1,2-dimethyl dimethanol, ethylene glycol and tetraethyl titanate are added into a reaction kettle, and an esterification reaction is carried out under a nitrogen pressure of 0.5 MPa, the esterification temperature is 230-280°C, and the temperature of the esterification distilled water is controlled at 120-130°C; when the water output reaches 94% of the theoretical value, the esterification is completed; after the esterification reaction is completed, the product is introduced into a polycondensation kettle, and then slowly evacuated to a vacuum degree of no more than 40 Pa, polycondensed at about 270-290°C for 3h, and after breaking the air, the material is discharged under stirring, and pelletized and dried to obtain copolyester slices; the molar ratio of terephthalic acid: cyclohexane-4-ene-1,2-dimethyl dimethanol: ethylene glycol: tetraethyl titanate is 1:0.4:0.8:0.
01.
2. The polyester plastic imitation stainless steel coated wire according to claim 1, characterized in that: The metal wire is one of iron wire, steel wire, galvanized iron wire and galvanized steel wire.
3. The polyester plastic imitation stainless steel coated wire according to claim 1, characterized in that: The colorant is one of a white colorant, a red colorant, and a yellow colorant; the plastic production additive is a lubricant pentaerythritol stearate; and the plastic functional additive is an antioxidant 168.
4. The polyester plastic imitation stainless steel coated wire according to claim 1, characterized in that: The thickness of the inner plastic coating layer (2) is 0.02-2 mm.
5. The polyester plastic imitation stainless steel coated wire according to claim 1, characterized in that: The thickness of the outer plastic coating layer (3) is 0.02-1 mm.
6. The polyester plastic imitation stainless steel coated wire according to claim 1, characterized in that: The cross-sectional area of the metal wire (1) is 0.05-100 mm 2 .
7. The polyester plastic imitation stainless steel coated wire according to claim 1, characterized in that: The cross section of the plastic-coated wire is circular, elliptical, triangular, C-shaped, rhombus-shaped or trapezoidal.
8. The method for preparing a polyester plastic imitation stainless steel coated wire according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Preparation of the raw material for the inner plastic coating layer (2): the following components are mixed uniformly according to weight: 87-99.99 parts of PET plastic particles, 1-3 parts of quartz sand, and 0-2 parts of plastic production additives to prepare the raw material for the inner plastic coating layer (2), and added to the extruder 1. The temperature of the extruder 1 is set to 120-350° C.; S2. Preparation of the raw material for the outer plastic coating layer (3): the following components are mixed uniformly according to weight: 87-99.99 parts of polyethylene terephthalate / cyclohexane-4-ene-1,2-dimethyl terephthalate copolyester, 0.01-3 parts of a colorant, 0-2 parts of a plastic production additive, and 0-2 parts of a plastic functional additive to prepare the raw material for the outer plastic coating layer (3), and added to the extruder 2. The temperature of the extruder 2 is set to 110-250° C.; S3, the plastic coating layer raw materials prepared in steps S2 and S3 are extruded through a double-channel composite die head, the inner channel is the raw material of the inner plastic coating layer (2), and the outer channel is the raw material of the outer plastic coating layer (3), and the metal wire (1) is passed through the middle of the discharge port of the extruder composite die head so that the outer side surface of the metal wire (1) is evenly coated with the inner plastic coating layer (2) and the outer plastic coating layer (3); S4, sending the metal wire (1) wrapped with the inner plastic coating layer (2) and the outer plastic coating layer (3) into water at 5-35°C for cooling and winding to complete the preparation of the polyester plastic imitation stainless steel plastic coated wire.
9. The method for preparing the polyester plastic imitation stainless steel coated wire according to claim 8, characterized in that: During the preparation of the polyester plastic imitation stainless steel coated wire, the metal wire (1) advances at a speed of 50-300 m / min.
Citation Information
Patent Citations
Impact-resistant modified PET (polyethylene terephthalate) engineering plastic and preparation method thereof
CN107353607A
High-wear-resistance injection-molded crocheted net wire as well as preparation method and application thereof
CN111763420A